COBRA VENOM AND ITS HEALTH BENEFITS - Monica Dinu; Olimpia Dumitriu Buzia; Irinel Lungu; Cristina Bazbanela; Dorin Ioan Cocoș (Romanian Journal of Medical and Dental Education, 2023)
The healing capacity of the venom has been known since antiquity, the snake became a symbol of medicine and pharmacy. The paper is a review of snake venom, especially cobra venom, and its benefits for human health. A summary of current progress in studying pharmacological effects and mechanisms of action following the administration of cobra venom was analyzed and achieved. The new approaches in the field provide a short-chain α-neurotoxin called cobrotoxin, present in the composition of the venom of the Naja naja atra, through the numerous proven pharmacological activities: anti-inflammatory, immunoprotective, analgesic, antiviral, could be effective in preventing and alleviating the symptoms caused by VOCID-19. The novelty of our study is to highlight the action of cobra venom in the treatment of patients with VOCID-19 or to inhibit SARS-COV-2 infection.